Losing A Language: A Qualitative Study of Code-Switching Among Taiwanese-Chinese Bilingual Aphasic Speakers with Selective Recovery Pattern - Chen, Jui Hua (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
This study aimed to investigate whether Taiwanese-Mandarin bilingual aphasia with selective recovery patterns lose knowledge of the inaccessible language or the control of the language they speak. Four patients were requested to narrate pictures in two separated language settings. The speech data collected in the clinical setting were compared with ten healthy bilingual adults’ speech data. The healthy bilingual adults did not code-switch in L2 but L1, which may be due to the language shift phenomenon in their lives. There were quantitative and qualitative differences of code-switching between the two groups. For the quantitative differences, the greater amount of code-switching observed in patients indicated that they did not lose knowledge of the inaccessible language, but rather the control of the language they spoke, and this may result from the impairment of the control mechanisms. Also, for the qualitative differences, the healthy adults code-switched more on nouns than verbs because those were frequently-used nouns in L2, and there were no equivalent translations in L1 ; on the contrary, the patients code-switched more on verbs than nouns and this may be due to the mapping word and referent is less transparent for verbs than it is for concrete nouns